Analisis Fiqih Muamalah Terhadap Akad Bagi Hasil Dalam Usaha Pertanian Jagung Di Bandung - Fathuya ZN Azizah; Muhibba (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
This research is based on the widespread practice of profit-sharing in the agricultural sector, particularly in maize farming, involving farmers and investors. The aim of this study is to examine the alignment between the profit-sharing contracts implemented and the principles of Islamic muamalah fiqh. The method used is qualitative research with a case study approach, involving in-depth interviews with maize plantation entrepreneurs in Bandung and analyzing them through the perspective of muamalah fiqh. The research findings show that the majority of the profit-sharing contracts implemented are still in accordance with sharia principles, although there are some discrepancies in the aspects of transparency and risk distribution that need improvement. In conclusion, although the profit-sharing contracts in the maize plantation business in Bandung generally do not contradict muamalah fiqh, improvements in the implementation and understanding of the principles of prudence and justice are still needed to minimize potential disputes and injustices in the future.